Scrutinizing the FDI Spillovers Model: Do Foreign Firms Motivate Local Firms to Export? - Yasin, Mohammad Zeqi; Purwono, Rudi (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2024)
We investigate the impact of foreign direct investment (FDI), particularly through multinational companies (MNCs), on the export behaviour and intensity of local firms. Focusing on the food and beverage subsectors in Indonesia from 2008–2015, we use the Heckman Selection model.We found a significant positive effect of FDI on the decision to export and the level of export intensity among domestic firms. The presence of MNCs in Indonesia appears to encourage local firms to both initiate and increase their export. Moreover, we observe a trend of export persistence, suggesting that firms active in exporting in one year are more likely to continue doing so in the following year. Other variables such as wages, import penetration, firm size, productivity, capital, and the presence of foreign firms were also included, with some influencing the decision to export more than the export intensity. Our findings provide some policy implications, namely for Indonesia’s “Making Indonesia 4.0” strategy in the food and beverages sectors, emphasizing the need for government support and human capital development to maximize the benefits of these spillovers.